Surgical Excision of Intradural Extra Medullary Spinal Tumors; Review of Outcome and Complications (Journal of Fatima Jinnah Medical University, 2018)
Objectives: Intradural extra medullary (IDEM) tumors of the spinal cord are most common benign lesions. Surgical decompression and resection, though challenging, benefits the patient significantly. Methods: The authors performed a retrospective review of forty three patients with IDEM lesions, who presented to the Department of Neurosurgery Shaikh Zayed Hospital Lahore from June 2006 to March 2014. All patients were clinically evaluated for preoperative neurological status and investigated with MRI without and with contrast. Postoperative complications were assessed along with the neurological status till the patients last follow up. Other complications including CSF leakage, requiring lumbar drainage and infections were also noted. Results: There were forty three patients with a mean age of 40 years. Complete resection was achieved in 38 (88.3%) patients and subtotal resection in 5 (11.6%) patients. Majority of the patients (41 out of 43) showed improvement (95%). Thirty eight patients were ambulatory post resection. Conclusion: IDEM lesions pose significant challenge for surgical resection. However if complete resection is achieved, the results, as evident by the functional recovery, are gratifying.
Keywords: Spine, Tumor, Intradural, Extramedullary, Resection Outcome